Anion Sensing by Fluorescent Expanded Calixpyrroles. Issue 19 (6th March 2018) - Pushina, Mariia; Koutnik, Petr; Nishiyabu, Ryuhei; Minami, Tsuyoshi; Savechenkov, Pavel; Anzenbacher, Pavel
Abstract: Expanded calixpyrrole‐type macrocycles, calix[2]benzo[4]pyrroles, bearing fluorescent moieties attached via conjugated vinyl spacers, have been synthesized from the corresponding formyl derivatives through Knoevenagel condensation. The anion‐binding properties of the resulting fluorescent macrocycles have been studied by means of NMR, UV/Vis, and fluorescence spectroscopies. Our main focus has been on dicarboxylates matching the size of the binding cavity of the calix[2]benzo[4]pyrrole skeleton. The observed anion‐binding properties were compared with those of the regular calix[4]pyrroles bearing identical fluorophores. Surprisingly, the parent calix[4]pyrroles appear to be equally efficient, if not more so, for sensing anions such as dicarboxylates. Affinity constants determined for various anions and dianions show the sensorsS1 –S5 to be highly cross‐reactive. The cross‐reactivity of the sensors was utilized in a microchip‐based array, which showed perfect (100 %) classification of 18 analytes utilizing only five sensors. Finally, the same array was used to quantitatively analyze dicarboxylates such as oxalate and malonate. The data from the array were subjected to linear regression, allowing the determination of various concentrations of dianions with low error (<2 %). Abstract : Macrocycle‐based anion sensing : Expanded calixpyrrole‐type macrocycles, calix[2]benzo[4]pyrroles, bearing fluorescent moieties attached via vinyl spacers, have been synthesized from the corresponding formyl derivatives through Knoevenagel condensation. The resulting highly cross‐reactive fluorescent chemosensors have been used to sense anions in water, including dicarboxylates such as oxalate and malonate (see graphic), in qualitative and quantitative analyses using polymer‐based microarrays.